1992
DOI: 10.1002/ijc.2910510604
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer in argentina. II: Risk from fibre, fat and nutrients

Abstract: A case-control study has been conducted to investigate the relationship between total energy intake, fibre and nutrients and colon cancer in Argentina. Cases are 110 newly diagnosed patients from 10 hospitals between 1985 and 1986. Two neighbourhood controls per case were matched on age, sex and place of residence. The intake of calories, fibre and nutrients was estimated from the information collected on food consumption during the 5-year period up to 6 months prior to interview of subjects, based on a pilot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 19 publications
(22 reference statements)
1
6
0
1
Order By: Relevance
“…Most of the previous studies have found no association between retinol intake and colorectal cancer in either men or women or in both sexes combined in Western countries (14)(15)(16)(17) and China (18). A case-control study showed an inverse association between retinol intake and colon cancer in men and women combined in Canada, but the investigators did not taken into consideration confounding of other dietary factors (28).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Most of the previous studies have found no association between retinol intake and colorectal cancer in either men or women or in both sexes combined in Western countries (14)(15)(16)(17) and China (18). A case-control study showed an inverse association between retinol intake and colon cancer in men and women combined in Canada, but the investigators did not taken into consideration confounding of other dietary factors (28).…”
Section: Discussionmentioning
confidence: 94%
“…Because provitamin A carotenoids are converted to retinol in the intestine and other tissues, total vitamin A intake has been estimated in most previous studies on diet and cancer (6,7). A limited number of studies has examined the relation between dietary retinol and colorectal cancer, reporting mostly a null association with dietary intake of retinol (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…The intake of vegetables, fish and poultry was associated, in the highest compared with the lowest quartile, with decreasing risk (ORs of 0.075, 0.39, and 0.39, for the three foodstuffs) (39,40).…”
Section: Dietary Factorsmentioning
confidence: 94%
“…In countries where people have adopted Western diets, the incidence of colorectal cancer is increasing. Argentina, in the central temperate region of South America, has important ethnic and geographical variations and was a suitable setting for case‐control studies into the risk of cancer in relation to diet and other lifestyle factors . Several studies produced original data on colorectal cancer and urinary tract tumors .…”
Section: Obesity and Comorbiditiesmentioning
confidence: 99%